EFFECTIVENESS OF GROUP COUNSELING WITH SELF MANAGEMENT TECHNIQUES TO IMPROVE ACADEMIC RESPONSIBILITY OF STUDENTS - Damayanti, Rida; Istati, Mufida (CV. TOTUS TUUS, 2024)
Academic responsibility is closely related to learning achievement at school, low academic responsibility will have a bad impact on students if it is constantly allowed to affect the learning process and reduce student learning outcomes so that potential development is not achieved properly and even a decrease in achievement. This study aims to determine the level of academic responsibility before and after the service is provided and the effectiveness of group counseling with self management techniques. The results showed that there was an increase in academic responsibility before and after being given treatment using group counseling with self management techniques, from 58% to 88%. Group counseling with self management techniques is effective for increasing students academic responsibility with the results of the paired T test with a sig value of 0.000 <0.05 so that Ha can be accepted. The percentage of students academic responsibility increased by 30% after treatment.